M&A, uncertainty, and bargaining power: Evidence from the German retail sector - Mayra Rebolledo (Westfälische Wilhelms-Universität Münster, Centrum für Angewandte Wirtschaftsforschung (CAWM), 2020)
Market concentration has been suggested as an enhancer of bargaining power imbalances for vertical commercial relationships. However, the empirical literature has not yet explored in which way this market concentration, as a result of -for instance- a M&A operations, could affect the negotiations with agents in vertical related markets; in particular, in frictional multiproduct commercial relationships, in which uncertainty may play a role of such negotiations. The present work proposes an explanation to this matter, by analyzing the strategic incentives and uncertainties that arise in this kind of commercial relationships from the announcement of an horizontal M&A operation, and the way these expectations could influence the bargaining power redistribution among players after the operation; opening the discussion on a dynamic analysis of bargaining outcomes.
Keywords: 330; Übernahme; Entscheidung unter Unsicherheit; Verhandlungsmacht; Verhandlungstheorie; Unternehmenskonzentration; Theorie; Einzelhandel; Deutschland